As the world turns implications of global shifts in higher education for theory, research and practice - Allen, Walter R.; Teranishi, Robert T.; Bonous-Hammarth, Marguerite (Bingley, U.K. : Emerald, 2012)
As the World Turns" examines two of the major problems confronting higher education in this modern world: access to higher education remains a persistent problem for disadvantaged students around the world; universities that are highly segregated by race, culture, language, nationality, or immigration status have lower achievement for disadvantaged students - who are also more often targets of discrimination. This volume compares discriminated, underrepresented and excluded groups in universities around the globe; identifying personal, group, institutional and societal factors related to persistent inequality. Through a consortium of international scholars, the chapters present studies on minority student experiences and achievement, asking whether and how universities: exhibit difference, diversity and inequality; integrate multiple social groups; encourage respect between diverse communities; and use diversity to enhance student learning. This volume demonstrates how diversity and equity help advance academic excellence in global higher education.
Introduction to section one / Marguerite Bonous-Hammarth -- The political economy of higher education / Francisco López Segrera -- Gender and access in commonwealth higher education / Louise Morley -- Water, water everywhere but not a drop to drink : higher education access and success for black and Latino students in California, USA / Walter R. Allen, Uma Jayakumar -- The political economy of social stratification in higher education : the situation in Japan / Akira Arimoto -- Comparing access to higher education in Brazil and India using critical race theory / Loni Bordoloi Pazich, Robert T. Teranishi -- Introduction to section two / Marguerite Bonous-Hammarth -- Massification of higher education in China and Japan in the comparative perspective / Futao Huang -- Equity and unrestricted access in the Argentine university system / Silvina Gvirtz, Betina Duarte -- Higher education studies : toward a new scholarly discipline / Andrey V. Rezaev, Olga V. Maletz -- Polish higher education : from state toward market, from elite to mass education / Renata Siemienska, Dominika Walczak -- "Highway to freedom" : African Americans in World War II China, the Gillem Board, the Ledo Road and U.S. racial integration / Geraldine H. Seay -- Introduction to section three / Robert T. Teranishi -- Thinking styles, culture, and economy : comparing Tibetan minority students with Han Chinese majority students / Li-fang Zhang, Gerard A. Postiglione, Ben Jiao -- Talking back to the colonial experience : creating an indigenous framework for education / Patricia Maringi G. Johnston -- The university of the West Indies : diversity and change / Patricia Anderson, Julian Devonish -- Accessing higher education, affirmative action and structured inequality : Indian experience / Govardhan Wankhede -- Minority student success in southwest China : identity work and its structural supports / MaryJo Benton Lee, Li Hong, Luo Lihui -- Introduction to section four / Robert T. Teranishi -- Approaching diversity work in the university : lessons from an American context / Anthony Lising Antonio, Jeffrey F. Milem, Mitchell J. Chang -- A northwest African American student center : is the support apocryphal? / Johnny D. Jones -- Unsettling spaces : higher education institutions in the United Kingdom / Deborah Phillips -- Practicing what we preach : racial and ethnic school composition, educational practice, and student achievement in California / Marguerite Bonous-Hammarth.
Includes index.
Print version record
Keywords: Education -- Research; Education -- Comparative; Education -- Aims & Objectives; Literacy strategies; Philosophy & theory of education; Discrimination in higher education; Education, Higher; International education